2018
DOI: 10.3324/haematol.2018.195552
|View full text |Cite
|
Sign up to set email alerts
|

Association of anemia with health-related quality of life and survival: a large population-based cohort study

Abstract: Anemia is highly prevalent, especially in older individuals. In selected populations, anemia has been reported to be associated with impaired survival and health-related quality of life. However, data on this impact in the general population are rare. Furthermore, discussions on the optimal definition of anemia have not been conclusive. We investigated these issues using survival data, scores from a health-related quality of life questionnaire (RAND-36), and hemoglobin concentration from 138670 subjects, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
111
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 41 publications
6
111
0
7
Order By: Relevance
“…This holds true if anaemia is defined with age‐independent lower limits as suggested by the WHO, but some increase in risk is already observed with haemoglobin concentrations in the low‐normal range at least in women (i.e., HB 120–130 g/l). Interestingly, a similar phenomenon was not found in individuals below the age of 60 in one population‐based study (Wouters et al , ), but was also observed in younger individuals in another study (Lee et al , , ). In 2019, Wouters et al grouped individuals by the type of anaemia according to additional serum measurements into anaemia of nutritional deficiency (including iron deficiency), anaemia of chronic inflammation, and unexplained anaemia, and found that anaemia of chronic inflammation is strongly correlated with inferior quality of life and increased mortality, whereas the influence of anaemia of other causes is much less pronounced (Wouters et al , ).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This holds true if anaemia is defined with age‐independent lower limits as suggested by the WHO, but some increase in risk is already observed with haemoglobin concentrations in the low‐normal range at least in women (i.e., HB 120–130 g/l). Interestingly, a similar phenomenon was not found in individuals below the age of 60 in one population‐based study (Wouters et al , ), but was also observed in younger individuals in another study (Lee et al , , ). In 2019, Wouters et al grouped individuals by the type of anaemia according to additional serum measurements into anaemia of nutritional deficiency (including iron deficiency), anaemia of chronic inflammation, and unexplained anaemia, and found that anaemia of chronic inflammation is strongly correlated with inferior quality of life and increased mortality, whereas the influence of anaemia of other causes is much less pronounced (Wouters et al , ).…”
Section: Discussionsupporting
confidence: 60%
“…Having established a physiological drop of haemoglobin with increasing age, this leads to a conflict with results from several studies showing an association between anaemia and morbidity and mortality in the elderly (Culleton et al , ; Penninx et al , ; Lee et al , ; Wouters et al , ). According to these studies, anaemic elderly individuals have an increased risk of death in the following years even after correction of major confounding factors.…”
Section: Discussionmentioning
confidence: 98%
“…Two independent consecutive lymphoma cases carry an identical MYD88 mutation but differ in their IGVH rearrangement Several studies have provided evidence of the presence of lymphoma stem cells by showing the apparent transmission of premalignant lymphoid cells in allogeneic bone marrow transplantation, where the donor and recipient develop the same lymphoid disease. [1][2][3][4][5][6] The lymphoid neoplasms do not develop at the same time, and in some cases, a different immunoglobulin heavy chain (IgH) rearrangement occurs in the two tumours. These data support the theory of a common lymphoma precursor cell (CPC) and make it less likely that it is due to a circulating donor tumour cell.…”
mentioning
confidence: 99%
“…2 In this issue of Haematologica, Wouters and colleagues report the results of the large Lifelines Cohort Study, confirming that anemia in the elderly is negatively associated with either quality of life or survival. 4 A key point of anemia in the elderly lies in the difficulty of establishing the etiology, which in turn should drive its management. While anemia in young people is generally due to a single cause (e.g.…”
mentioning
confidence: 99%
“…2 The mitochondrial-ER interface, commonly referred to as the mitochondria-associated membrane (MAM), is a proteinaceous tether facilitating bidirectional communication between the two organelles controlling the balance between survival and death. 3,4 The exchange of metabolites and contact at the interface controls energy produc-…”
mentioning
confidence: 99%